FRI0429 Dysregulation of the splicing machinery in leukocytes from ankylosing spondylitis patients is associated to disease pathogenesis. (15th June 2017) - Jimenez-Gomez, Y; Lopez-Pedrera, C; Pedraza-Arévalo, S; del, M Río-Moreno; Άbalos-Aguilera, MC; Ruiz-Limon, P; Perez-Sanchez, C; Castro, MC; Barbarroja, N; Rosa, I Arias-de la; Font, P; Escudero, A; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease, of unknown aetiology, associated to the development of several comorbidities such as atherosclerosis. Splicing is a post-transcriptional process involved in the RNA maturation. Recent studies have revealed that a pathological dysregulation of the splicing machinery or spliceosome is associated to several human diseases. Yet, the spliceosome alterations have not been described in AS. Objectives: 1) To analyze whether dysregulation of the spliceosome is present in AS. 2) To evaluate the association between the alteration of this process and the clinical, inflammatory, oxidative, and atherogenic profiles present in this pathology. Methods: Fourteen AS patients and 14 healthy donors (HDs) were included in the study. Disease function and activity status were analyzed using the BASFI and BASDAI. The expression of selected components of the major-(n=12) and minor-spliceosome (n=4), and splicing factors (n=28) was evaluated in purified monocytes, lymphocytes and neutrophils from patients and HDs (n=14 each) by Fluidigm methodology. Oxidative stress, inflammation and atherogenesis were evaluated by flow cytometry and RT-PCR. Endothelial function was determined by the post occlusive hyperaemia test using Laser-Doppler. Results: Compared to HDs, a significant dysregulation in the expression of relevant splicing factors and spliceosome components was found in all the leukocyte subtypes from AS patients, being neutrophils which displayed higher number of altered molecules. Interestingly, a specific altered profile of major- and minor-spliceosome members, and splicing factors was observed when compared lymphocytes (U4, U6, NOVA1, RMB17), monocytes (PRP8, SF3B TV2, CELF4, ESRP2, RBM3, SAM68 TV1, SRSF10, TIA1) and neutrophils (U11, U2, U2AF2, U11, CA 150, ESRP1, PSF, PTB, SRM160). Correlation studies revealed that disease activity (CRP, ESR, BASDAI) was associated to the alteration of a vast number of spliceosome components in the three subtypes of analyzed leukocytes. In addition, the BASFI index correlated with the expression of splicing factors ESRP1, SRSF1 and TRA2B in neutrophils. The inflammatory, atherogenic and oxidative profile of AS leukocytes was related to the expression of a number of spliceosome molecules in the three leukocyte subsets, although neutrophils exhibited the highest number of deregulated spliceosome components related to inflammation (STAT3, TNF-α, IL-1α, IL-1β, IL-5) and cell adhesion (ICAM-1, SELL, THBS4, CDH5). Finally, endothelial dysfunction correlated with the expression of several components of the major-spliceosome and splicing factors in monocytes and neutrophils. Conclusions: 1) AS patients display a dysregulation of the splicing machinery components associated to disease function and activity. 2) The expression of spliceosome members in the different leukocyte subsets is related to the inflammatory, oxidative and proatherogenic profile of AS patients. Alteration of the spliceosome may provide new biomarkers for diagnosis and clinical monitoring of AS Acknowledgements: Funding by: JA PI-0314–2012, SER, ISCIII (RIER RD16/0012/0015) Disclosure of Interest: None declared